Application of mid‐infrared free‐electron laser for structural analysis of biological materials. (8th December 2020) - Kawasaki, Takayasu; Zen, Heishun; Ozaki, Kento; Yamada, Hironari; Wakamatsu, Kazumasa; Ito, Shosuke
Abstract : A mid‐infrared free‐electron laser was applied to the structural analysis of biological fossils. Infrared microscopy and far‐infrared spectroscopy following vibration mode selective irradiation clearly show the structural variation of fossilized inks from cephalopods. Abstract : A mid‐infrared free‐electron laser (MIR‐FEL) is a synchrotron‐radiation‐based femto‐ to pico‐second pulse laser. It has unique characteristics such as variable wavelengths in the infrared region and an intense pulse energy. So far, MIR‐FELs have been utilized to perform multi‐photon absorption reactions against various gas molecules and protein aggregates in physical chemistry and biomedical fields. However, the applicability of MIR‐FELs for the structural analysis of solid materials is not well recognized in the analytical field. In the current study, an MIR‐FEL is applied for the first time to analyse the internal structure of biological materials by using fossilized inks from cephalopods as the model sample. Two kinds of fossilized inks that were collected from different strata were irradiated at the dry state by tuning the oscillation wavelengths of the MIR‐FEL to the phosphoryl stretching mode of hydroxyapatite (9.6 µm) and to the carbonyl stretching mode of melanin (5.8 µm), and the subsequent structural changes in those materials were observed by using infrared microscopy and far‐infrared spectroscopy. The structural variation of these biological fossils is discussed based on the infrared‐absorption spectral changes that were enhanced by the MIR‐FEL irradiation, and the potential use of MIR‐FELs for the structural evaluation of biomaterials is suggested.